Influence of time-dependent material degradation on life cycle serviceability of interspersed railway tracks due to moving train loads. (15th November 2019) - Kaewunruen, Sakdirat; Ngamkhanong, Chayut; Ng, Jipong
Highlights: Interspersed track systems are simulated using nonlinear finite element method. Ballast model using tensionless stiffness has been adopted to reflect the real-world physical behaviour. 600 nonlinear simulations varying various time-dependent parameters have been carried out. Dynamic uplifts are the source of rapid track deterioration over life cycle. More routine ballast tamping is recommended to resolve any track geometry problem. Abstract: Presently, timber-sleepered tracks are still being adopted in railway networks transporting goods and passengers. However, the deterioration of timber sleepers is evident after years of service due to natural decay; and it is difficult to seek cost-effective hardwood sleepers to replace the aging sleepers. An impermanent "interspersed" approach is an alternative method used to substitute rotten timbers with concrete sleepers. Although the interspersed tracks offer a cost-effective short-term solution for certain track classes, there are some drawbacks to this practice, since the interspersed track has inconsistent stiffness problems, and the different track decay rate can cause uneven settlement and foundation failure, which can lead to significant track deterioration over time. The emphasis of this study is placed on the long-term behaviour of interspersed track components under repeated train loading. Interspersed track models in three-dimensional space have been developed and validated using a finite element method. The effects of deteriorated railway components (timber, rail pads, ballast) are taken into account to examine the dynamic performance of the interspersed tracks under moving train loads. This study will help rail track engineers better understand the time-dependent behaviour of interspersed tracks, enable a truly predictive track maintenance and improve the reliability of infrastructure asset maintenance and life cycle management.